Impact of Social Media Usage on Civic Engagement towards Societal Problems: Qualitative Modelling Approach - Lu shao; Mahendar Goli; Abatihun Alehegn Sewagegn; Anoop Kumar Sahu (Discrete Dynamics in Nature and Society)
Civic engagement participation in solving the social problems gained momentum among social media users. It is probed via literature survey that many research studies conducted in understanding the civic behaviour and personality development; therefore, research documents were found still limited in the area of factors and their constructive factors (hypotheses) identification towards intensifying the online civic engagement for solving and reforming the society. Therefore, the purpose of the research is directed to build a qualitative research model of crucial factors by using the social capital theory, developing constructive factors (hypotheses) based on the research model, and testing constructive factors, which could intensify the civic engagement of online social media user’s (Facebook, Twitter, etc.) towards solving the social problems. To fulfil aforesaid agendas, the authors employed the qualitative survey method, which consisted of a simulation of an online survey against H1–H8 hypotheses of the research model. The survey data was collected by exploring the Google Form under the five-point Likert scale as a data collection tool. Participated students were prioritized from a metro city of India on a purposive mode. Collected usable samples of 341 students were considered for descriptive analysis such as reliability, validity, content, and construct of factors of the research model. Next, confirmatory factor analysis was performed to measure of fitness of factors of the research model. Finally, structural equation modelling (path analysis) carried out to assess the constructive factors (hypotheses) of research model. The summary of the results stated that usage of social media, trust, civic skills, and social responsibility are found as global significant factors, which affected an individual’s civic engagement in solving the social problems. This study aids the practitioners and academicians to audit and evaluate the advanced factors and their constructive factors in future, which affect the young social media users’ civic engagement in solving the social problems.